STUDENTS’ COMPETENCE IN TRANSLATING RECOUNT TEXT AT KHAIRUN UNIVERSITY - Wallu, Andini; Latif, Saiful; Firmansyah, Firmansyah; K, Sy Kurniati (Universitas Khairun, 2025)
This study aimed to analyze the types of errors made by students in translating texts. The research involved 22 students from class B, semester 5 in the English Education Study Program at Khairun University. This research employed a qualitative method to identify and categorize the translation errors made by the students. The findings revealed four types of errors: omission, addition, misformation, and misordering errors. The results showed that 11.7% of students made omission errors, while 7.8% made addition errors, making it the least frequent error type. Misformation errors were found in 19.5% of students. The most dominant type of error was misordering errors, which occurred in 61% of students. Among all the identified errors, misordering errors were the most frequent type found in class B, semester 5 students. The findings indicate that misordering errors significantly affect the accuracy and clarity of students' translations.